Risk of re-emergence of COVID-19 after exit from lockdown - Lopez, Leonardo (Henry Stewart Talks, 2020)
Type of modelling and initial research rationale, Reliability of modelling results, Caution to be applied when analysing and interpreting results of models, Measures to avoid second wave of infection, Conditions that could lead to a second wave, Role of acquired immunity in the dynamics of a second wave